1996
DOI: 10.1177/107424849600100108
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of Myocardial Infarct Size in the Rabbit by a Carbohydrate Analog of Sialyl Lewisx

Abstract: BACKGROUND: Available data suggest that the accumulation of neutrophils within the myocardium following an ischemic event plays an important role in the pathogenesis of myocardial ischemia/reperfusion injury. It is of interest, therefore, to develop pharmacologic agents designed to inhibit neutrophil adhesion to the endothelium. METHODS AND RESULTS: A synthetic carbohydrate analog to the P-selectin ligand sialyl Lewis(x) (sLe(x)) was evaluated for its ability to protect the myocardium from ischemia/reperfusion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

1998
1998
2007
2007

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 31 publications
1
6
0
Order By: Relevance
“…4). This observation is consistent with previous reports (Kilgore et al 1996(Kilgore et al , 1998, in which neutrophil accumulation in the area-at-risk was observed during the 30 min of myocardial ischemia and 5 h of reperfusion in a similar rabbit model. SM-20550 attenuated the neutrophil accumulation in the area-at-risk without affecting the level of neutrophils in the non-ischemic area (Fig.…”
Section: Discussionsupporting
confidence: 94%
“…4). This observation is consistent with previous reports (Kilgore et al 1996(Kilgore et al , 1998, in which neutrophil accumulation in the area-at-risk was observed during the 30 min of myocardial ischemia and 5 h of reperfusion in a similar rabbit model. SM-20550 attenuated the neutrophil accumulation in the area-at-risk without affecting the level of neutrophils in the non-ischemic area (Fig.…”
Section: Discussionsupporting
confidence: 94%
“…GM2296, fucose-carbon-glycyrrhetinic acid, was constructed to contain the necessary carboxylic acid and a carbon fucoside, and would be expected to have the ability to flex enough to fit all three selectins. Although in vivo data with these compounds are limited, both GM1380 and GM1292 have been shown in vivo to reduce myocardial infarct size in a rabbit ischemia model (35,36).…”
Section: Discussionmentioning
confidence: 99%
“…Although a considerable number of these studies showed a clear effect on infarct size [29][30][31][32][33][34], some reports, however, failed to show any effect of antineutrophil measures on reperfusion injury [62][63][64]. infarct size).…”
Section: Discussionmentioning
confidence: 99%
“…Whereas an inflammatory response normally benefits the host by eliminating host invaders, in the case of ischaemia it is directed against the host-tissue and will contribute to further tissue injury [26]. In addition, it has been demonstrated in animal models that neutrophil depletion and several types of antineutrophil therapy reduce infarct size in postischaemic reperfusion injury [29][30][31][32][33][34]. In addition, it has been demonstrated in animal models that neutrophil depletion and several types of antineutrophil therapy reduce infarct size in postischaemic reperfusion injury [29][30][31][32][33][34].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation